Fish Nutrition - Ruth Francis-Floyd (EDIS)
For many years water quality has been the most important limitation to fish production. Advances in life support technology have been substantial in recent years, and nutrition is increasingly regarded a key limitation to increased production efficiency as well as the growth and propagation of “new” species. This document is VM114, one of a series of the Fisheries and Aquatic Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 12, 2002.